Anti-Neutrophil Cytoplasmic Antibody in Behçet’s Disease - Duzgun, Nursen (Master Publishing Group, 2006)
Anti neutrophil cytoplasmic antibody (ANCA) is strongly associated with some vasculitic disorders. Behçet’s disease (BD) is a systemic vasculitis of unknown etiology. In this study, ANCA was found to be positive in 8 out of 66 patients (10.2%) with BD by combination testing consisting of immunofluorescence and ELISA [one patient showed an atypical pattern by indirect immunofloresence techique, 6 patients were reactive to bacterial-permeability increasing protein (BPI) and one patient was reactive to Cathepsin G in ELISA]. There were no vascular manifestations such as veneous or arterial thrombosis and arterial aneurysms in ANCA-positive patients with BD. The results suggest that ANCA may be found in a minority of BD as those in previous published studies.